A Rapid Direct Telomerase Assay Method Using 96-Well Streptavidin Plates - Rawle Francis; Simon H. Friedman (BioTechniques)
We have developed a high-throughput direct assay method for the assay of telomerase activity that improves on previous direct telomerase assays in two ways that allow larger numbers of samples to be conveniently processed: (i) 96-well streptavidin coated plates are used to bind and wash biotinylated primer extension products from the telomerase assay, as opposed to tubes containing streptavidin-coated magnetic beads; and (ii) storage phosphorimagery is used instead of film autoradiography to detect telomerase products after being washed and released from the streptavidin- derivatized matrix. This method improves on previous direct assay methods using magnetic beads by allowing larger numbers of samples to be conveniently assayed. Also, the total activity of the radiolabeled nucleotides used in this procedure is significantly lower than that used in standard direct telomerase assays, lowering costs and exposure to radioactivity. We have validated the assay by repeating, in triplicate, the IC50 determination of rivanol, our previously identified telomerase inhibitor.